Answer: C
Step-by-step explanation:
You can write each term into a fraction.
becomes ![x^4^/^5](https://tex.z-dn.net/?f=x%5E4%5E%2F%5E5)
When you multiply 2 terms with the same base, you add the exponents.
![x^4^/^5*x^4^/^5=x^4^/^5^+^4^/^5=x^8^/^5](https://tex.z-dn.net/?f=x%5E4%5E%2F%5E5%2Ax%5E4%5E%2F%5E5%3Dx%5E4%5E%2F%5E5%5E%2B%5E4%5E%2F%5E5%3Dx%5E8%5E%2F%5E5)
is also the same as ![x\sqrt[5]{x^3}](https://tex.z-dn.net/?f=x%5Csqrt%5B5%5D%7Bx%5E3%7D)
You get this because
. When you pull out 5 os x, you are left with x³ on the inside.
Answer: dont know just search it up
Answer:
Step-by-step explanation:
By the Pythagorean Theorem
h^2=x^2+y^2
Which means that the hypotenuse (longest side of a right triangle) squared is equal to the sum of its squared sides. In this case we are given the side lengths of 8 and 15 feet.
h^2=8^2+15^2
h^2=64+225
h^2=289
h=17 ft
The ladder is 17 feet long.
Answer:
234.5
Step-by-step explanation: